Perceptions Regarding Health Services Willingness to Pay - Rahman, Aditya Safarudin; Anas, Muhammad; Amalia, Nuke (Universitas Muhammadiyah Semarang, 2025)
Background: Healthcare systems worldwide face escalating costs and resource allocation challenges, making willingness to pay (WTP) a crucial economic evaluation tool for understanding patient preferences and informing healthcare policy decisions.Objective: This systematic literature review examined perceptions regarding health services' willingness to pay across diverse healthcare contexts.Methods: Following PRISMA guidelines, a systematic search was conducted using PubMed, Scopus, and Web of Science databases. Studies published between 2024 and 2025 examining perceptions of health services WTP were included. Data extraction focused on study characteristics, methodologies, and key findings regarding WTP determinants.Results: Seventeen studies from 11 countries were included, comprising ten cross-sectional studies, two mixed-methods studies, and various other designs. Key findings revealed that WTP is influenced by sociodemographic characteristics (age, gender, education, income), service-specific attributes (preventive vs. treatment services), and perceptual dimensions including perceived value, risk assessment, and trust. Educational attainment and income consistently emerged as positive predictors of WTP across different health services. Conclusion: WTP for health services represents a complex phenomenon mediated by perceptual factors beyond traditional economic considerations. Healthcare financing strategies should incorporate perception-focused interventions to align WTP with actual costs and improve healthcare accessibility.